MENINGKATKAN PARTISIPASI BELAJAR PESERTA DIDIK MELALUI METODE PERMAINAN PESAN BERANTAI PADA MATA PELAJARAN PPKN KELAS X-4 SMAN 1 PONOROGO - Lutfiana Arriza Novianti; Oksiana Jatiningsih; Edy Purnomo (Institute Agama Islam Al-Qolam Malang, 2023)
This study aims to increase student learning participation through the chain message game method in PPKn class X-4 SMAN 1 Ponorogo subjects. This Classroom Action Research uses a chain message game learning method. The population in this study was 36 students of grade X-4 SMA Negeri 1 Ponorogo. The results showed an increase in student participation through the chain message game method in PPKn class X-4 subjects of SMA Negeri 1 Ponorogo in the first cycle of the cooperation indicator by 83.3%, the indicator of answering questions by 33.3% and the indicator of expressing opinions by 27.8% While in the second cycle the indicator of cooperation by 100%, the indicator of answering questions by 69%, and the indicator of expressing opinions by 61.1%. Cycle I and cycle II in the indicators of cooperation increased by 16.7%, answered questions increased by 35.7%, and expressed opinions by 33.3%. These results show that the learning method of chain message games is able to increase student learning participation.